Policy Strategy for Accelerating the Clean and Serving Bureaucratic Region (Wbbm) at Mpp Bale Madukara Purwakarta - Anne Ratna Mustika; R. Widya Setiabudi Sumadinata; Sinta Ningrum (Green Publisher Indonesia, 2024)
This research aims to identify the policy acceleration strategy for a Clean and Serving Bureaucratic Area at MPP Bale Madukara, Purwakarta Regency. The study was conducted using a qualitative method, involving interviews and literature review of the research object. Based on the research results, several aspects still need improvement to enhance services at MPP Bale Madukara, Purwakarta Regency. The policy acceleration strategy for the Clean and Serving Bureaucratic Area (WBBM) based on the theory by Wheelen and Hunger in Ade Irawan (2015: 45) at MPP Bale Madukara still requires strengthening in strategy formulation and strategy implementation. Regarding strategy formulation, there is a need for improvements in governance, such as work programs and specific SOPs for MPP Bale Madukara. In terms of strategy implementation, while the overall performance of DPMPTSP is very good, specific performance measurement for MPP Bale Madukara has not been conducted yet, and evaluation and control from all tenants at MPP Bale Madukara are necessary.